Where in Europe is Carmen Sandiego? - Peel, John, 1954- ([Racine, Wis.] : Western Pub. Co., 1991)
Members of Carmen Sandiego's gang have struck again! This time they've taken four of Europe's greatest treasures-- the Parthenon, the Little Mermaid, Johann Sebastian Bach's harpsichord, and the original copy of Auld lang syne. Only you can capture the gang and return the stolen property, but which treasure will you recapture first?
"Golden"--Cover.
Includes collectible and score cards.
Keywords: Carmen Sandiego (Game); Sandiego, Carmen (Fictitious character) -- Juvenile fiction; Plot-your-own stories; Europe -- Description and travel -- Juvenile fiction